Lietuvių kalbos būdvardžių su priesaga *-lo- raida - Ambrazas, Saulius (Baltistica, 2006)
DEVELOPMENT OF LITHUANIAN ADJECTIVES WITH THE SUFFIX *-lo-A lot of traits of archaic merger of the adjective suffixes *-lo-, *-no- and *-ro- have been attested in Lithuanian, cf. Lith. leĩ-las ‘slender, slim, thin’ (Latv. liels ‘big’), Lith. leĩnas ‘thin, flexible’ (OIc. linr, MIr. lían ‘soft’) and Gk. λειρός ‘lean, thin; pole; weak’; Lith. tuk-lùs, tùk-nas, tuk-nùs and tuk-rùs ‘fat’. The synonymic usage of derivatives with -lus (-ì) and -nus (-ì) is especially characteristic of Lithuanian, cf. kim-lùs (-ì) and kim-nùs (-ì) ‘hoorse, raucous’, patrauk-lùs (-ì) and patrauk-nùs (-ì) ‘attractive, winning’ a. o.On the other hand, in Lithuanian deverbal adjectives with the old suffix -las (-a) are going to become extinct under the press of very productive corresponding derivatives with the derivational ending -us (-i). A little more new adjectives are formed with -lus (-i) (i. e. with u-stem variant of the old suffix -las) but the great part of them have equivalents in -us (-i), cf. dyg-lùs (-ì) and dyg-ùs (-ì) ‘mickly’ tįs-lùs (-ì) and tįs-ùs (-ì) ‘extensive, lengthy’ a. o.Very few adjectives with the suffixes, based on *-lo-, are formed from nouns in Lithuanian. Some of them also have correspondences in other Indo-European languages, cf. Lith. ak-ýlas ‘sarp-sightedlant’ : akìs ‘eye’ and Lat. cīv-īlis ‘civic, civil’ : cīvis ‘citizen’.
Keywords: lietuvių kalba; būdvardis; -lo- priesaga